PENINGKATAN PRODUKSI DAN PENDAPATAN USAHATANI SALAK SUWARU - Tri Sudaryono (Jurnal Ilmiah Hijau Cendekia, 2017)
Salacca zalacca is one of fruit in Indonesia and in others areas, Salacca zalacca is a superior fruit which have market oriented in national and international. One of areas in East Java which is the center of Salacca zalacca production is Malang Regency with the famous varieties “Suwaru”. Varieties “Suwaru” as one of East Java's superior fruit has been released as a superior variety, it have the most of thick flesh meat, masir, sweet, aromatic and it’s weight between 70 - 120 g. Given its economic value, efforts to increase production and farm income of Salacca zalacca varieties Suwaru need to be done. The purpose of this research is to know the effect of water supply and ZA fertilization on the production and increase income farmer of Salacca zalacca variety “Suwaru” in Suwaru Village, Pagelaran Sub-district, Malang Regency from April 2012 until August 2013. The result of this research shows that the increase of production and income farmer of Salacca zalacca variety “Suwaru” can be reach with giving water and ZA fertilization. Water supply and ZA fertilization can increase the production of Salacca zalacca variety “Suwaru” up to two-fold. In the way the giving ZA fertilization, income farmer of Salacca zalacca variety “Suwaru” can be increased up to three-fold.